The last kids on Earth - Brallier, Max (Brallier, Max. Last kids on Earth, 2015)
"After a monster apocalypse hits town, average thirteen-year-old Jack Sullivan builds a team of friends to help slay the eerily intelligent monster known as Blarg"--